Factors influencing the demand for individual voluntary private health insurance in Iran - Rajabali Daroudi; Reza Hashempour; Behzad Raei; Sajad Ramandi; Kamran Irandoust; Ali Kazemi-Karyani; Nasrin Abolhasanbeigi Gallehzan; Jafar Yahyavi Dizaj; Marjan Darabi (Cost Effectiveness and Resource Allocation)
Abstract Background Financial risk protection is one of the main goals of healthcare systems worldwide and prepayment system plays an important role to achieve it. There are some prepayment schemes, and Individual voluntary private health insurance (IVPHI) as a way can be affected by some variables. Objective This study aimed to investigates the factors affecting the purchase and selection of IVPHI coverage in Iran. Methods This study used secondary data from a private insurance company in Iran, collected in 2023. Data were retrospectively gathered via an online questionnaire covering demographics, health status, and lifestyle factors used to assess risk for voluntary health insurance plans. Individuals with high-risk profiles were referred to the company’s physician for a clinical examination, after which they were categorized into high-risk or low-risk groups. The insurer then decided whether to approve the purchase of individual supplementary health insurance (ISHI). After data extraction and cleaning, a multivariate logistic regression model was used to identify determinants of voluntary health insurance purchase. Results Most ISHI sales occurred in low-deprivation provinces (71%), with women (64%) and those aged 26–49 (70%) more likely to purchase. Higher coverage (Plan 4) was preferred across all age groups. Key factors influencing ISHI purchase included health status, basic insurance, and region, with moderate deprivation areas showing higher demand for higher coverage plans. Conclusion The findings emphasize regional, demographic, and health status disparities in ISHI purchases. Policymakers should focus on improving access to higher coverage plans, especially in more deprived areas, to ensure equitable insurance distribution.